Examining The Indonesian Chinese Portrait: Ethnic Chinese Minority in a Muslim-majority Country - Soenjoto, Wening Purbatin Palupi; Mahmudah, Siti Nur (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
In 1998, Indonesian students demonstrated reforms that demanded every aspect of Indonesian life. By such moral strength, they succeeded in changing every basis of freedom for the people; Democracy. During the recovery of the Indonesian economic crisis and reforms, in May 1998, the most tragic riots occurred and the recovery that occurred against Indonesians was raised by Chinese. After the economic crisis in 1998, it couldn’t be denied that Indonesia's economic and political problems were in poor condition. This research uses qualitative research with a case study approach. The results of the study stated that since May 1998, the Indonesian Government has given Indonesians more freedom to speak openly, to gather in political parties. Most importantly, one of the laws states that no one is against Chinese descent. Those who value Indonesia automatically become Indonesian citizens without native (non-indigenous) recognition. The minority of citizens of Chinese descent after the 1998 riots slowly began to be recognized and became a force in the economic movement carried out by citizens of Chinese descent in Indonesia. The political relationship between Indonesia and China has become a force recognized by the world in a symbiotic relationship of mutualism in the economic and political fields.